Mitigasi Cekaman Salinitas pada Fase Perkecambahan Kedelai melalui Invigorasi dengan Ekstrak Kulit Manggis dan Ekstrak Kunyit: Mitigasi Cekaman Salinitas pada Fase Perkecambahan Kedelai melalui Invigorasi dengan Ekstrak Kulit Manggis dan Ekstrak Kunyit - Maman Suryaman; Ida Hodiyah; Yeni Nuraeni (Universitas Bangka Belitung, 2021)
The germination period is a critical phase of abiotic stress, including salinity stress. Invigoration can be done to reduce the effect of salinity stress and speed up the germination process. This research was aimed to find out the effect of invigoration to mitigate salinity stress of soybean seed germination. This research was conducted in the Greenhouse of Faculty of Agriculture, Siliwangi University. The experiment was arranged in a randomized block design with factorial patterns and three replications. First factor was the level of salinity of seawater, consisted of 3 levels ( 0% = EC= 0,6 mS cm-1; 10% =EC = 7,69 mS cm-1 ;and 20% = EC =11,4 mS cm-1). The second factor was invigoration, which consisted of 4 levels (water as control, mangosteen peel extract, turmeric extract, and mixture of mangosteen peel extract + turmeric extract with a ratio of 1:1). Results showed that there was no interaction effect between the invigoration and salinity stress on all parameters observed, but there was an independent effect of invigoration on soybean vigor and salinity stress. The salinity stress had a significant negative effect on seed germination. The invigoration of mangosteen peel extract or turmeric extract was able to maintain soybean seed vigor under salinity stress conditions. Therefore the invigoration could mitigate the effect of salinity stress of soybean seed germination.